Faktor-Faktor yang Mempengaruhi Permintaan Daging Sapi Potong pada Konsumen Rumah Tangga di Wilayah Timur Kabupaten Cirebon - Maulana, B; Perwitasari, F D; Bastoni, B (PETERPAN (Jurnal Peternakan Terapan), 2025)
Beef is one of the most nutritious foods that fulfill people's protein needs after chicken and milkfish. Cirebon Regency has many migrants, both workers and students, so the demand for beef is high. This study aims to determine the characteristics of beef consumers and analyze the factors that influence beef demand. The research was conducted by purposive sampling used to select research locations in Pabuaran Kidul Market and Ciledug Market with a sample size of 100 respondents. The lemeshow formula was used as a sample for respondents. This research uses quantitative descriptive analysis method and multiple linear regression with the help of IBM SPSS 26. Normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test are used for classical assumption testing, while F test and t test are used for hypothesis testing. The results of the study of factors that significantly affect beef demand are income with a sig value of 0.000 < 0.05, the number of family members with a sig value of 0.003 < 0.05 and the price of beef with a sig value. 0.006 < 0.05, consumer age with sig value 0.012 < 0.05. Broiler price, milkfish price, and education level did not significantly affect beef demand. The price elasticity of beef shows that the demand for meat is elastic, the cross-elasticity of broiler chicken and milkfish shows that beef is a substitute good, the income elasticity shows that beef is a normal good.